ANTIOXIDANT POTENTIAL AND HEALTH BENEFITS OF PURPLE SWEET POTATO LEAVES (IPOMOEA BATATAS L.) - Suciati, Tri; Septadina, Indri Seta; Msy Rulan Adnindya; Ilyah Abdullah, Nour (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Free radicals are molecules with one or more unpaired electrons, which makes them very labile and reactive. They are important in tissue damage and pathological processes in living organisms. Endogenous sources of free radicals are metabolic waste, such as combustion processes in the body, proteins, carbohydrates, and fats that we consume, and exogenous ones that come from air pollution, vehicle exhaust, and various chemicals and ultraviolet rays. 1, 2 An increase in free radicals can cause oxidative stress, resulting in oxidative damage from the cellular tissue to organ levels that will accelerate aging and cause various disease pathogenesis. 3 To reduce the impact of oxidative stress, adequate antioxidants are needed, which can be obtained from the body through enzymes or natural antioxidant intake. 4 One source of natural antioxidants comes from the leaves of purple sweet potato plants (Ipomea batatas L), which contain chemical compounds such as beta-carotene, bioflavonoids, catechins, and polyphenols that can ward off free radicals, improve oxidative stress conditions so that they are beneficial for maintaining health.